A conceptual framework for evaluating higher education institutions. Issue 6 (8th August 2016) - Chinta, Ravi; Kebritchi, Mansureh; Ellias, Janelle
Abstract : Purpose: Performance evaluation is a topic that has been researched and practiced extensively in business organizations but has received scant attention in higher education institutions. A review of literature revealed that context, input, process, product (CIPP) model is an appropriate performance evaluation model for higher education institutions. However, little guidance exists for choosing appropriate metrics and benchmarks in implementing the CIPP model. The purpose of this study was to develop a framework using CIPP model for performance evaluation of higher education institutions. Design/methodology/approach: To achieve the purpose of the study, a review of literature was conducted to identify an appropriate evaluation model. Then metrics and benchmarks framework were formed based on practical approaches used in a large university in the United States. Findings: Nine perspectives in performance evaluation using the CIPP model and their application in higher education institutions were developed and discussed. The discussion provides examples, relative prevalence including frequency of usage, advantages and limitations of each of the nine perspectives of performance evaluation in higher education institutions. An actual application of the suggested CIPP model in the United States largest university, by student enrollment, was provided. Implications for institutional assessment and continuous improvement for higher education institutions were made. Originality/value: The study provides a practical framework, model, and guidelines that can be used by higher education institutions to evaluate and enhance their performances and better prepare students to effectively work in society.